(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Solubility, the process by which a solute dissolve in a solvent to create a homogenous solution, is one of the crucial elements in attaining the ideal medicine concentration in the circulating system for the desired pharmacological effect. It's that simple action. Insufficient water solubility is the main issue with formulation development. A significant difficulty for formulation scientists is solubility. Any medicine that is to be absorbed must be present in solution at the absorption site. Particle size reduction, crystal engineering, salt creation, solid dispersion, application of surfactants, complexation, and other techniques like these are used to increase the solubility of poorly soluble pharmaceuticals. These approaches also involve physical and chemical drug modification. The choice of a solubility-improving technique is influenced by the drug's properties, the site of absorption, and the necessary dosage form and properties. The paper provides detailed information on solubility enhancement techniques, as well as the importance of solubility and the latest approaches to increasing solubility.